Analisis Pengetahuan dan Sikap tentang HIV/AIDS dan Bahaya Narkoba pada Siswa Laki-laki MAN 1 Medan Tahun 2016 - nur azizah; Sori Muda Sarumpaet; Rahayu Lubis (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2016)
ABSTRACT Human Immunodeficiency Virus continues to be a global public health problem, there are 36,9 million people living with HIV by two millions new infections in 2014. The percentage of drug users living with HIV by 18,8%. The causes of AIDS 15,2% because of injecting drug, while HIV patients was 7,7% in Indonesia. Prevention of HIV/AIDS and the dangers of drugs can be done by improving knowledge and attitudes. This study aims to determine the level of knowledge and attitudes about HIV/AIDS and the dangers of drugs in MAN 1 Medan students. This type of research was analytic survey with cross sectional design. The population were all male students of XI MAN 1 Medan. The samples were 132 students. The sampling technique was using Simple Random Sampling. The collected data were primer data which analyzed with Fisher's Exact test. The results of the univariate analyzed were level of HIV/AIDS knowledge was enough (38.6%), the knowledge of the dangers of drugs was less (43.2%), the attitude of HIV/AIDS was less (71.2%) and the attitude of the dangers of drugs was good (96.2%) in MAN 1 Medan. The Fisher’s Exact test result showed that there was a significant relationship between knowledge and attitudes about HIV/AIDS (p=0,020), there was no significant relationship between knowledge and attitudes about dangers of drugs (p=1,000), there was no significant relationship between knowledge about HIV/AIDS and knowledge about dangers of drugs (p=0,735), there was no significant relationship between attitudes about HIV/AIDS and attitudes about dangers of drugs (p=0,764). Average knowledge of HIV/AIDS and the dangers of drugs students are enough. Expected to the head master to improve students’ knowledge and attitudes about HIV/AIDS and the dangers of drugs in MAN 1 Medan through health education such as schools cooperate with the community health centre or BNN to do counseling about HIV/AIDS and the dangers of drugs at least once in a semester.   Keywords: HIV/AIDS, Drug, level of knowledge, attitude